Suicidal Ideation and Associated Factors Among Medical Undergraduates in A Medical College of North Kerala - Roshni SS; Remya Ramachandran; Chalil, Swathi; KrishnaRaj JS (National Journal of Medical Research, 2025)
Background: Suicide is a major global concern, causing over 700,000 deaths annually and ranking as the fourth leading cause of death among 15-29-year-olds. Medical students are at heightened risk, with thoughts of suicide often emerging at the beginning of their medical education. Identifying and addressing this issue by finding out the prevalence of suicidal ideation and associated factors among medical undergraduates was the main aim of our study. Methodology: A Cross-sectional study was conducted in medical colleges of Kozhikode district, North Kerala using World Mental Health survey initiative version of the World Health Organization Composite International Diagnostic Interview (WHO-CIDI). Students from all academic years who were willing to participate were included through consecutive sampling. Results: The study found that 28.9% of medical students experienced suicidal ideation after enrolling in medical school. Substance abuse, h/o psychiatric illnesses in students, comorbidities, sleeping difficulties, psychiatric illnesses in family, suicides in family and experiencing stressful events during the course were factors significantly associated with suicidal ideation. Conclusions: This study observed a high prevalence of suicidal ideation among medical students. And the factors associated were joining MBBS without self-interest, substance abuse, history of psychiatric illness, psychiatric illness in the family, stressful events, co-morbidities and sleeping difficulties.